Apoptotic Donor Cells in Transplantation - Husain, Irma; Luo, Xunrong (Frontiers in Immunology, 2021)
Despite significant advances in prevention and treatment of transplant rejection with immunosuppressive medications, we continue to face challenges of long-term graft survival, detrimental medication side effects to both the recipient and transplanted organ together with risks for opportunistic infections. Transplantation tolerance has so far only been achieved through hematopoietic chimerism, which carries with it a serious and life-threatening risk of graft versus host disease, along with variability in persistence of chimerism and uncertainty of sustained tolerance. More recently, numerous in vitro and in vivo studies have explored the therapeutic potential of silent clearance of apoptotic cells which have been well known to aid in maintaining peripheral tolerance to self. Apoptotic cells from a donor not only have the ability of down regulating the immune response, but also are a way of providing donor antigens to recipient antigen presenting cells that can then promote donor-specific peripheral tolerance. Herein, we review both laboratory and clinical evidence that support the utility of apoptotic cell-based therapies in prevention and treatment of graft versus host disease and transplant rejection along with induction of donor-specific tolerance in solid organ transplantation. We have highlighted the potential limitations and challenges of this apoptotic donor cell-based therapy together with ongoing advancements and attempts made to overcome them.